2001
DOI: 10.1016/s0885-3924(01)00339-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Delirium on the Circadian Distribution of Breakthrough Analgesia in Advanced Cancer Patients

Abstract: Most cancer patients will experience pain requiring opioid therapy during their illness. Standard opioid therapy includes fixed scheduled doses and so-called "rescue" doses for breakthrough pain. Circadian rhythms seem to influence the expression of pain and the responsiveness to analgesic medication. Delirium is a common complication in advanced cancer patients and it also may modify the expression of pain and the use of analgesic medication. We reviewed the circadian distribution of breakthrough analgesia (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…[1][2][3][4] The presence of delirium can interfere with the recognition and control of physical and psychological symptoms such as pain. 5,6 Delirium is often under-recognized or misdiagnosedinpatientswithcancer;evenwhenrecognized, it frequently goes untreated or is inappropriately treated. Clinicians who care for patients with cancer must be able to diagnose delirium accurately, undertake appropriate assessment of etiologies, and understand the risks and benefits of the pharmacologic and nonpharmacologic interventions currently available for managing delirium.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The presence of delirium can interfere with the recognition and control of physical and psychological symptoms such as pain. 5,6 Delirium is often under-recognized or misdiagnosedinpatientswithcancer;evenwhenrecognized, it frequently goes untreated or is inappropriately treated. Clinicians who care for patients with cancer must be able to diagnose delirium accurately, undertake appropriate assessment of etiologies, and understand the risks and benefits of the pharmacologic and nonpharmacologic interventions currently available for managing delirium.…”
Section: Introductionmentioning
confidence: 99%
“…1 Delirium in patients with cancer has been associated with adverse outcomes, including decreased performance status 2 ; increased pain and use of breakthrough analgesia 3,4 ; longer length of hospital stay 5,6 ; increased distress for the patient, spouse, caregivers, and nurses [7][8][9] ; and decreased survival.…”
Section: Introductionmentioning
confidence: 99%
“…Because circadian rhythms may influence pain expression, delirium can alter the normal circadian rhythm and may modify the pain expression. It was found that patients without delirium tended to use more breakthrough medication in the morning and those with delirium used more medication in the evening and at night, which was consistent with their reversal of normal circadian cycling [47]. When observing patients who have an increased need for breakthrough medication in the evening more so than in the morning, practitioners should remember that this may herald the development of overt delirium.…”
Section: Delirium and Dementia At The End Of Lifementioning
confidence: 73%